(untitled) (Research, Society and Development, 2022)
The search for forage cultivars that provide higher yields with quality in periods of forage shortage, whether in isolated or mixed management, is essential for livestock stability. Thus, the objective was to evaluate the forage performance and nutritive value of rye cultivars mixtures (BRS Progresso, BRS Serrano and Temprano) from different production cycles compared to the isolated management of rye, dual-purpose wheat cvs. (BRS Tarumã and BRS Pastoreio) and black oat cv. Embrapa 139 Neblina as controls. The experiment was conducted at a randomized complete block design, with four rye associations and the isolated cultivation of wheat, oat, and rye. Dry matter (DM) yield and nutritive value, such as content of neutral detergent fiber (NDF), acid detergent fiber (ADF), and crude protein (CP) content were evaluated for each cut and total values. There was difference (P<0.001) in total DM, the highest yield was in single cultivation as well as mixtures with Temprano. BRS Serrano and BRS Progresso and their mixture had lower leaf blade percentage in the total DM. There were differences (P<0.05) in NDF concentration (55.1 to 70.60%), ADF (15.2 to 34.7%), and CP (27.4 to 36.8%) levels along harvests. Among cultivars, Temprano showed the highest proportion of leaf blades and total DM yield.